Theoretical studies of the local structures and EPR parameters for Cu²⁺ center in Cd₂(NH₄)₂(SO₄)₃ single crystal - Li, Ch.-Y.; Chen, L.-B.; Mao, J.-J.; Zheng, X.-M. (Condensed Matter Physics, 2015)
The electron paramagnetic resonance (EPR) parameters (g factors gi and the hyperfine structure constants Ai, i = x, y, z) are interpreted by using the perturbation formulae for a 3d⁹ ion in rhombically (D₂h) elongated octahedra. In the calculated formulae, the crystal field parameters are set up from the superposition model, and the contribution to the EPR parameters from the admixture of d-orbitals in the ground state wave function of the Cu²⁺ ion was taken into account. Based on the calculation, local structural parameters of the impurity Cu²⁺ center in Cd₂(NH₄)₂(SO₄)₃ (CAS) crystal were obtained (i.e., Rx ≈ 2.05 Å, Ry ≈ 1.91Å, Rz ≈ 2.32 Å). The theoretical EPR parameters based on the above Cu²⁺-O²⁻ bond lengths in CAS crystal show a good agreement with the observed values. The results are discussed.